2019
DOI: 10.1186/s12888-019-2136-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of prolonged grief disorder in a sample of female refugees

Abstract: Background: Prolonged Grief Disorder (PGD) is a distinct syndrome that follows bereavement. It is different from other mental disorders and is characterized by symptoms such as yearning for the bereaved, or intense emotional pain or distress. Violent loss is one major risk factor for the development of PGD. Objectives: PGD has been studied in different populations, mostly in small samples, with only a few of them being representative. Although research highlighted that traumatic experiences paired with challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Previous studies using the PG-13 scale among refugees and conflict-affected populations have reported rates of PGD ranging from 8 to 34.6% (19,23,(69)(70)(71). Again, a comparison is difficult as respective study samples differ substantially from ours in terms of age, gender, or setting.…”
Section: Thoughts On the Prevalence Of Pgdmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies using the PG-13 scale among refugees and conflict-affected populations have reported rates of PGD ranging from 8 to 34.6% (19,23,(69)(70)(71). Again, a comparison is difficult as respective study samples differ substantially from ours in terms of age, gender, or setting.…”
Section: Thoughts On the Prevalence Of Pgdmentioning
confidence: 68%
“…Considering the high prevalence of PGD among refugees and its association with psychological comorbidity and functional impairment (20,71), early detection and adequate treatment are essential. Left untreated, individuals suffering from PGD might remain with high levels not only of psychological (20,76), but also of physical distress (69,70,73), as well as with an increased risk of suicide (70,73,77).…”
Section: Discussionmentioning
confidence: 99%
“…Refugees are often exposed to war, political instability, violence, and displacement in their country of origin (Fazel et al., 2005), rendering them a highly vulnerable population. This vulnerability is reflected in high rates of estimated psychological disorders among refugees during the postsettlement period, namely posttraumatic stress disorder (PTSD), which affects 8%–37% of refugees (Slewa‐Younan et al., 2015), depression (28%–75%; Slewa‐Younan et al., 2015), anxiety (21%; Alexander et al., 2013), and prolonged grief disorder (9%; Steil et al., 2019), the large between‐study variability in estimates notwithstanding.…”
mentioning
confidence: 99%
“…Many refugees report traumatic experiences and deaths of loved ones are among the most frequently reported events [e.g., ( 3 )]. Accordingly, the prevalence of prolonged grief disorder (PGD) in refugee samples is high [e.g., ( 4 , 5 )]. PGD is a new diagnosis in ICD-11 and DSM-5-TR that is characterized by persistent and pervasive yearning for a deceased person and/or pre-occupation with this person that persist for an uncharacteristically long time (>6 months in ICD-11; ≥12 months in DSM-5-TR) ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%